Advances in cancer research. - Vande Woude, George F.; Klein, George (Advances in cancer research, 2010)
Advances in Cancer Researchprovides invaluable information on the exciting and fast-moving field of cancer research. Here, once again, outstanding and original reviews are presented on a variety of topics, including.